OPTIMASI ALUR PERBAIKAN KENDARAAN UNTUK MENGATASI KEMACETAN DAN PEKERJAAN TAMBAHAN DI BENGKEL INTERNAL PT XYZ DENGAN VALUE STREAM MAPPING (VSM) - Shandy Andreas Nugroho Purnomo; Indro Kirono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to enhance the efficiency of the vehicle repair workflow at the internal workshop of PT XYZ, with a focus on addressing process congestion and unplanned additional work. Key issues identified include the high volume of incoming vehicles exceeding service capacity, delays in removing completed units, and inconsistencies in the initial inspection process. These conditions have prolonged repair lead times, reduced workshop throughput, and weakened the operational readiness of the logistics fleet. This research adopts a qualitative case study approach, with data collected through direct observation, work order documentation analysis, and interviews with technicians and quality control personnel. The workflow was mapped to identify bottlenecks, and root cause analysis was conducted to determine the underlying drivers of congestion and the frequent occurrence of additional repair work. The results show that congestion is driven by unmanaged vehicle inflow, limited workshop space, and inefficient post-repair handover procedures. Additional work commonly arises from insufficient initial inspections, hidden component failures, and non-standardized working methods among technicians. The study recommends implementing more rigorous inspection procedures, reorganizing workshop layout, adopting a digital work order tracking system, and establishing standardized coordination mechanisms aligned with global logistics best practices